How Tourism Quality Creates Satisfaction from the Perspective of International Tourists - Kakeesh, Dana; Ahmed, Ala'eddin (Jordan Journal of Business Administration, 2020)
The purpose of this study is to investigate tourism quality, as represented by software components of tourist satisfaction, loyalty and WOM in Jordan, from the perspective of international tourists. Further, purposive sampling technique was employed in this study. A structural model and regression weight analysis show the impact of software components on tourist satisfaction. A structured questionnaire was distributed to a sample of 384 foreign tourists who had experience of the Jordanian tourism sector, where 247 questionnaire forms were found to be usable, representing 64.%. The software components were found to have a significant effect on tourist satisfaction. From the study findings, some implications are proposed, including a recommendation to improve the quality of information, services, hospitality, safety and security of the Jordanian tourism sector, regularly and continuously. Further recommendations are suggested to help practitioners compete successfully in the tourism industry.